Analisis Perawatan Heading Machine dengan Metode Reliability Centered Maintenance (RCM) - Danang Risky Suhadi; Kris Witono (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
The heading machine is a critical type of machine used in the production of header tubes. If a failure occurs during the production of header tubes, the product cannot proceed to the next process and must be discarded. However, this machine frequently encounters component failures that require halting the machine for repairs, which is detrimental to the company. This research aims to enhance the machine's reliability by identifying the critical components and scheduling appropriate maintenance based on the heading machine's needs. The research method used is RCM, which includes collecting data on machine downtime and repairs, creating an FMEA table, identifying critical components, calculating TTF and TTR, determining component distribution patterns, establishing parameters, calculating the reliability of critical components, and scheduling maintenance. The research findings identified the critical components as conical spring for orifice and jaw for thread. The calculation of the reliability value using the Weibull distribution equation with scale and shape parameters for the conical spring for orifice components are 1001.78 and 1.12285, respectively. For the jaw for thread component, the scale and shape parameters are 532.083 and 1.33233, respectively, based on values derived from statistical software. As a result, the maintenance schedule should be set when the reliability value of the conical spring for orifice and jaw for thread reaches 0.5 at (t) 720 hours or 30 days, and (t) 390 hours or 17 days, respectively.